The Usages and Potential Uses of Alginate for Healthcare Applications - Mollah, M. Z. I.; Zahid, H. M.; Mahal, Z.; Faruque, Mohammad Rashed Iqbal; Khandaker, M. U. (Frontiers in Molecular Biosciences, 2021)
Due to their unique properties, alginate-based biomaterials have been extensively used to treat different diseases, and in the regeneration of diverse organs. A lot of research has been done by the different scientific community to develop biofilms for fulfilling the need for sustainable human health. The aim of this review is to hit upon a hydrogel enhancing the scope of utilization in biomedical applications. The presence of active sites in alginate hydrogels can be manipulated for managing various non-communicable diseases by encapsulating, with the bioactive component as a potential site for chemicals in developing drugs, or for delivering macromolecule nutrients. Gels are accepted for cell implantation in tissue regeneration, as they can transfer cells to the intended site. Thus, this review will accelerate advanced research avenues in tissue engineering and the potential of alginate biofilms in the healthcare sector.